2005
DOI: 10.1007/11431053_2
|View full text |Cite
|
Sign up to set email alerts
|

Feta: A Light-Weight Architecture for User Oriented Semantic Service Discovery

Abstract: Abstract. Semantic Web Services offer the possibility of highly flexible web service architectures, where new services can be quickly discovered, orchestrated and composed into workflows. Most existing work has, however, focused on complex service descriptions for automated composition. In this paper, we describe the requirements from the bioinformatics domain which demand technically simpler descriptions, involving the user community at all levels. We describe our data model and lightweight semantic discovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
4
1

Relationship

4
5

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 12 publications
1
58
0
Order By: Relevance
“…By implementing MOBY Central specifically for the PlaNet consortium, the relevance of discovered services could be greatly enriched for consortium members. Through the ongoing collaboration with my Grid, who have designed an extremely rich ontology for describing Web Services, this limitation of MOBY Central is being addressed, and the search and discovery mechanisms in future iterations of MOBY should be much richer and more focused (Lord et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…By implementing MOBY Central specifically for the PlaNet consortium, the relevance of discovered services could be greatly enriched for consortium members. Through the ongoing collaboration with my Grid, who have designed an extremely rich ontology for describing Web Services, this limitation of MOBY Central is being addressed, and the search and discovery mechanisms in future iterations of MOBY should be much richer and more focused (Lord et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It has, however, been observed that bioinformatics web services have certain characteristics that can further hinder the process of their semantic annotation [2]. Since many services in the bioinformatics domain are developed on an as-needed basis, such web services typically have poor quality descriptions [3].…”
Section: Contextmentioning
confidence: 99%
“…Such software can output poor quality WSDL files in which operations, parameters and datatypes are given meaningless identifiers. Also, as a result of their ad hoc creation, such web services can be deployed with little or no associated documentation [2]. The lack of an agreed upon data model in bioinformatics also means that such web services usually have weakly typed web service operation parameters [4].…”
Section: Contextmentioning
confidence: 99%
“…As a second, more general-purpose option, a semantic discovery facility called Feta [12] also offered natively as part of the Taverna distribution. Feta includes a semantic service registry that maintains annotated description of services, and can be searched using terms from a publicly available ontology.…”
Section: Support For Service Discoverymentioning
confidence: 99%